Ornamental origins and genomic frontiers: a review of big-bracted dogwood research - Hamm, Trinity P.; Trigiano, Robert N.; Nowicki, Marcin; Moreau, Erin L. P.; Molnar, Thomas J.; Xiang, Qiu-Yun Jenny; Boggess, Sarah L.; Hewezi, Tarek; Klingeman, William E.; Hadziabdic, Denita; Staton, Margaret E. (Frontiers in Plant Science, 2026)
The big-bracted (Benthamidia) dogwood clade consists of small- to medium-sized deciduous trees within the genus Cornus, known for their showy spring-time floral bract display. Cornus is within the family Cornaceae and order Cornales, and as Cornales is one of the earliest diverging asterids, these taxa have been important for phylogenetic research. Three species within the big-bracted clade, flowering (Cornus florida), kousa (C. kousa), and Pacific (C. nuttallii) dogwoods, are popular ornamental landscape plants in North America, with more than 130 cultivars released. Despite their commercial popularity, numerous research gaps have limited the expansion of fundamental research and dogwood breeding programs. In this present review, we aim to provide a thorough overview of our current understanding of 1) the phylogenetic and biogeographic context, 2) plant biology and major pests and pathogens impacting commercialization, 3) historical commercialization and propagation methods, and 4) genetic and genomic resources and how they have been implemented to understand these species. Research gaps and future directions to advance basic research and breeding of big-bracted ornamental dogwoods are discussed throughout.